Anatomy Respect in Implant Dentistry. Assortment, Location, Clinical Importance (Review Article) - Rawaa Y Al-Rawee; Mohammed Mikdad Abdalfattah (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Aims: In this article; we will reviews critically important basic structures routinely encountered in implant therapy. It can be a brief anatomical reference for beginners in the field of dental implant surgeries. Highlighting the clinical importance of each anatomical structure can be beneficial for fast informations refreshing. Also it can be used as clinical anatomical guide for implantologist and professionals in advanced surgical procedures.  Background: Basic anatomy understanding prior to implant therapy; it's an important first step in dental implant surgery protocol specifically with technology advances and the popularity of dental implantation as a primary choice for replacement loosed teeth. A thorough perception of anatomy provides the implant surgeon with the confidence to deal with hard or soft tissues in efforts to restore the exact aim of implantation whether function or esthetics and end with improving health and quality of life. Collection and citation of more than eighty published articles discuss anatomical importance in implant dentistry and reviews the clinical importance of each landmarks can affect the dental implant procedures in different situations.  Conclusion: Though knowledge and understanding of the anatomical basics before surgery can reduces unsolicited complications and reducing the success criteria subsequently affect patients satisfactions. However, certain anatomic sites may be challenging concerning treatment plan as maxillary sinus area of inferior alveolar nerve area.